Analysis of the influence of renewable energy generation on market power. Issue 13 (19th January 2018) - Shang, Nan; Guo, Li; Ding, Yi; Lin, You; Liu, Lei; Shao, Changzheng; Song, Yonghua
Abstract : With the ever‐increasing integration of renewable energies (RES) into the power system, the bidding strategies and the market power of the conventional generating units are expected to change. Given that this study proposes a novel market power analysis model to identify the influence of RES on the market power of those conventional generation companies. Evidenced by the case studies, it can be found that the market power of the conventional generating units, referred to as the market revenue share, fluctuates with the variable power output of the RES. Moreover, it suggests that the system operators can closely monitor generation companies' market power change and mitigate their market power if necessary by means such as restricting their offers.